Efforts to Overcome Waste Accumulation to Keep the Environment Clean - Muhammad Baiqun Isbahi; Istianah Lizzah (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2023)
The public problem is waste management. The production of hamlets is the biggest amount of waste. Waste production in this hamlet continues to increase, but management is not yet running well and in a balanced manner. The accumulated and scattered waste is obtained from various sectors. This community service activity uses the PAR (Participatory Action Research) method. The PAR method is a research or research process that is oriented towards empowerment and change. Community service using the PAR method functions as a learning tool in overcoming problems and fulfilling the practical needs of the community. The realized work program involves the community as participants. So that the implementation of the program does not burden the community, but instead creates conditions that are built in a unity of mutual cooperation as a tradition that has been owned by the community all this time. The realization of the KKN activity program in Jedong Wetan Hamlet, namely counseling and mutual cooperation, Procurement of rubbish bins and warning signs, Utilization of plastic waste. During we underwent the KKKN program in Wotanmas Jedong village, we learned many things. Through this service activity, we can apply the knowledge we gain in college. However, it is not uncommon for being directly in the field to be very different compared to theoretical learning. This is a very valuable experience that we cannot find in lectures.